On a criterion of mutual adjointness for extensions of some nondensely defined operators - Storozh, O. G.; Oliiar, Iu. I. (Methods of Functional Analysis and Topology, 2014)
In the paper the role of initial object is played by a pair of closed linear densely defined operators L_0 and M_0, where L_0 M_0^*:= L, acting in Hilbert space. A criterion of mutual adjointness for some classes of the extensions of finite-dimensional (non densely defined) restrictions of L_0 and M_0 are established. The main results are based on the theory of linear relations in Hilbert spaces and are formulated in the terms of abstract boundary operators.